Karyoplast exchange between strontium- and 6-DMAP-parthenogenetically activated zygotes of cattle - Meo, Simone Cristina; Ferreira, Christina Ramires; Perecin, Felipe; Saraiva, Naiara Zoccal [UNESP]; Drummond Tetzner, Tatiane Almeida [UNESP]; Yamazaki, Walt [UNESP]; Verde Leal, Claudia Lima; Meirelles, Flavio Vieira; Garcia, Joaquim Mansano [UNESP] (Elsevier B.V., 2009)
Ooplasmic factors drive nuclear organization after fertilization and are also important for re-programming in nuclear transfer procedures, in which artificial activation is essential for reconstructed embryos to progress in development. The present research evaluated the effect of pronuclear transfer (PT) between zygotes parthenogenetically activated with ionomycin followed by strontium (S) or 6-DMAP (D) on early embryonic development. PT was performed in the same zygote to obtain embryos in control groups (S-PT and D-PT) and between zygotes activated with S and D to achieve embryos with differentially activated cytoplasm (C) and nucleus (N) (SCDN and DCSN). PT procedure did not affect cleavage and blastocyst rates, respectively, in PT control groups compared to non-manipulated control (S-PT: 73.6% and 7.3% compared with S-Control: 77.9% and 7.8%; and D-PT: 73.3% and 31.7% compared with D-Control: 83.1% and 41.5%). Cleavage, eight-cell, and blastocyst rates, respectively, were similar between SCDN (76.5%, 36.4%, and 6.8%) and DCSN (69.5%, 25.0%, and 4.9%) embryos. Developmental rates in SCDN were similar to S-PT, but inferior to D-PT. Developmental arrest up to eight-cell stage was greater in SCDN and DCSN than in S-PT and D-PT. In conclusion, karyoplast exchange between parthenogenetic zygotes activated with strontium and 6-DMAP can lead to nuclear-cytoplasmic incompatibilities and affect embryonic development to the eight-cell and blastocyst stages. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Artificial activation; Bovine; Embryonic development; Pronuclear transfer